Liposomal Delivery of Hepatoprotective Phytochemicals for Liver Diseases: Advances in Formulation, Targeted Delivery, and Clinical Translation - Dignesh Khunt; Jigna Khasiya; Sanjay Chauhan; Bhupendra G. Prajapati; Udaykumar Vegad; Sagar Salave (Biomedicines, 2026)
Background/Objectives: Chronic liver diseases (CLDs), including viral hepatitis, alcohol-related liver disease, non-alcoholic fatty liver disease, hepatic fibrosis, and hepatocellular carcinoma, account for approximately two million deaths annually and remain a global health challenge. Although phytochemicals exhibit antioxidant, anti-inflammatory, antifibrotic, and metabolic regulatory activities through modulation of Nrf2/Keap1, NF-κB/MAPK, TGF-β/Smad, and lipid metabolism pathways, their therapeutic translation is hindered by poor aqueous solubility, extensive first-pass metabolism, and low oral bioavailability. This review evaluates the potential of liposomal delivery systems to overcome these limitations and improve hepatic drug targeting. Methods: A structured narrative review was conducted using systematic literature search principles. PubMed/MEDLINE, Scopus, and Web of Science databases were searched for studies published between January 2000 and March 2025. Original research articles evaluating liposomal formulations of hepatoprotective phytochemicals were assessed with emphasis on formulation strategies, pharmacokinetics, therapeutic efficacy, targeting approaches, and translational potential. Results: Liposomal encapsulation frequently improved systemic exposure and, in several preclinical studies, increased oral bioavailability relative to free phytochemicals, although the magnitude of improvement varied substantially according to the compound, formulation, route of administration, and experimental model. Liposomal encapsulation also improved formulation stability and enabled controlled release in several studies. Surface engineering using polyethylene glycol and receptor-specific ligands, including galactose, lactobionic acid, glycyrrhetinic acid, and vitamin A, further improved circulation time and cell-specific hepatic delivery. Emerging technologies such as microfluidic manufacturing, biomimetic liposomes, and multifunctional formulations show promise for improving formulation reproducibility and therapeutic performance, although clinical evidence remains limited. Conclusions: Liposomal delivery represents a promising strategy for enhancing the pharmacokinetic performance and therapeutic efficacy of hepatoprotective phytochemicals. However, additional well-designed clinical studies, scalable manufacturing approaches, and regulatory standardization are required to facilitate successful clinical translation.